The Role of Probiotics in Modulating Immune Response in Allergic Rhinitis: A Literature Review - Inas Qonita; Joyce Caecilia Manullang; Rahelia Dwi Josephine Pandjaitan; Kezvia Khanza Quinn Fahira (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2026)
The Role of Probiotics in Modulating Immune Response in Allergic Rhinitis: A Literature Review Background: Allergic rhinitis is an inflammation of the nasal mucosa that occurs as a result of a hypersensitivity reaction mediated by immunoglobulin E (IgE) following exposure to allergens. This condition is commonly characterized by symptoms such as recurrent sneezing, rhinorrhea, nasal congestion, and nasal itching. The pathogenesis of allergic rhinitis involves complex immune responses, including mast cell activation, eosinophil infiltration, and the release of various inflammatory mediators. The complexity of these mechanisms has led to the development of therapeutic approaches that focus not only on symptom control but also on the modulation of immune responses, one of which involves the use of probiotics. Objective: To identify and understand the role of probiotics in modulating the immune response in allergic rhinitis. Literature Review: Probiotics have the potential to be used as an adjuvant therapy in allergic rhinitis due to their ability to modulate immune responses involved in the pathogenesis of the disease. Several probiotic strains, particularly from the genera Lactobacillus and Bifidobacterium, have been shown to regulate the Th1/Th2 balance, reduce the production of allergen-specific IgE, and enhance the activity of regulatory T cells that help suppress allergic inflammatory reactions. In addition, probiotic metabolites such as short-chain fatty acids (SCFAs) can inhibit inflammatory pathways and promote the production of anti-inflammatory cytokines. Findings from several clinical studies indicate that probiotic administration may help improve symptoms and quality of life in patients with allergic rhinitis, suggesting their potential use as an adjunct to conventional therapy. Conclusion: Probiotics have the potential to serve as a promising adjuvant therapy for allergic rhinitis through their immunomodulatory effects. However, their clinical effectiveness still depends on the specific strain, dosage, and duration of administration; therefore, further research is required to establish optimal therapeutic standards.